How New Zealand women experience their partners' imprisonment : a thesis presented in partial fulfilment of the requirements for the degree of Master of Arts in Psychology at Massey University - Crabtree, Angela J (My University, 2008)
In New Zealand in 2006 there were almost 6,000 men in prison, with predictions that the numbers may rise to 9,000 by the year 2010. Almost a quarter of those imprisoned men reported having a spouse or partner at home, and almost 600 reported one or more dependent children. This means that there are at least 2,500 women and children in New Zealand who are directly affected by the incarceration of their man. My aim in this research was to explore the impacts and meaning of imprisonment for those women whose partners are in prison, and thereby to contribute to an understanding of these impacts, stimulate debate, and draw attention to a silenced and undervalued population within our communities. In-depth, unstructured interviews were used to collect data from six women whose partners were in prison. lnterviews were recorded, transcribed, and analysed using a narrative approach of inquiry. Data analysis supports prior findings that the impacts of imprisonment of a partner are generally detrimental to women and families. The women interviewed reported difficulties related to their partners' imprisonment in almost every aspect of their lives: emotional, physical, financial, social and familial. There is currently little social, community, or government support for these women and families, despite the recognition that family well-being is critically important in reducing recidivism. I offer some recommendations for improving the situation for women whose partners are in prison, and make suggestions for future research.
Keywords: New Zealand; Prisoners' spouses; Interviews; Prisoners' families -- Effect of imprisonment on